2019
DOI: 10.1126/science.aau9343
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic sequencing at the epicenter of the Nigeria 2018 Lassa fever outbreak

Abstract: The 2018 Nigerian Lassa fever season saw the largest ever recorded upsurge of cases, raising concerns over the emergence of a strain with increased transmission rate. To understand the molecular epidemiology of this upsurge we performed, for the first time at the epicenter of an unfolding outbreak, metagenomic nanopore sequencing directly from patient samples, an approach dictated by the highly variable genome of the target pathogen. Genomic data and phylogenetic reconstructions were communicated immediately t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
192
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(220 citation statements)
references
References 27 publications
(28 reference statements)
13
192
0
6
Order By: Relevance
“…Due to the above advantages, Nanopore sequencing technology has been widely used in the field of epidemic outbreak investigation over the past 2 years to detect infectious pathogens, antimicrobial drug resistance and other infectious areas of concern. For the rapid and real‐time monitoring of outbreaks, researchers conducted real‐time dynamic genomic monitoring of the Lassa fever epidemic in Nigeria and the Guinea Ebola virus epidemic through a small portable Oxford Nanopore MinION device. Through the use of direct RNA sequencing, a team of microbiologist led by John Barnes of the US CDC sequenced the complete RNA genome of the influenza A virus using Nanopore .…”
Section: Application Status Of Sequencing Technology In Pathogenic DImentioning
confidence: 99%
“…Due to the above advantages, Nanopore sequencing technology has been widely used in the field of epidemic outbreak investigation over the past 2 years to detect infectious pathogens, antimicrobial drug resistance and other infectious areas of concern. For the rapid and real‐time monitoring of outbreaks, researchers conducted real‐time dynamic genomic monitoring of the Lassa fever epidemic in Nigeria and the Guinea Ebola virus epidemic through a small portable Oxford Nanopore MinION device. Through the use of direct RNA sequencing, a team of microbiologist led by John Barnes of the US CDC sequenced the complete RNA genome of the influenza A virus using Nanopore .…”
Section: Application Status Of Sequencing Technology In Pathogenic DImentioning
confidence: 99%
“…VSVΔG/LASVGPC has yet to be tested for efficacy against these isolates [29,30]. Nevertheless, these data support the feasibility of effectively protecting against multiple LASV lineages with a single vaccine.…”
Section: Vesicular Stomatitis Virus Vector Platformmentioning
confidence: 96%
“…During a 2014 outbreak of Lassa fever at tertiary hospitals in Ebonyi and Enugu in southeastern Nigeria, phylogenetic analysis of patient isolates provided strong support for the role of virus transmission between infected individuals [27]. The dramatic increase in cases during the 2018 Nigerian Lassa fever season launched investigations into the possible emergence of a new strain with a higher transmission rate [28,29]. Two sequencing studies, analysing 220 and 120 LASV genomes from infected patients, revealed high variability and derivation from previously circulating viruses rather than from a single dominant strain [29,30].…”
Section: Genetic Diversity and 2018 Nigerian Outbreakmentioning
confidence: 99%
See 2 more Smart Citations